Freelancing for television and radio - Mitchell, Leslie Scott, 1905- (London ; New York, NY : Routledge, 2005)
"'Freelancing for TV and Radio' is an indispensable guide for those either considering or currently working as a freelance media professional. It offers brief overviews of the TV and Radio industries as well as the role of convergence in video production and multi-media"--Provided by publisher.
Includes bibliographical references (p. 116-129) and index.